Pengaruh Penggunaan Multimedia Interaktif Berbasis Canva terhadap Keterampilan Membaca Awal Anak Usia Dini - Julisa, Regia; Saridewi; Serli Marlina; Nurhazizah (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
Early reading is an integrated activity that includes a number of activities, from recognizing letters, understanding words, reading letters along with the sounds and meanings contained, and drawing conclusions from a reading. One of the ICT media that is considered effective and interesting for developing children's early reading skills is Canva-based interactive multimedia. This media stimulates a learning experience that makes children happy, so that it can encourage their interest in learning, especially for those who experience delays in recognizing letters, words, and the relationship between sound and meaning. This study aims to investigate the extent to which Canva-based interactive multimedia influences children's early reading skills at Wahana Harapan Bangsa 1 Kindergarten, Padang City. The quantitative approach through its method is in the form of a quasi-experiment. Referring to the results of the post-test hypothesis test, a significance value of 136> 0.05 was obtained, which indicates that the data from both classes are homogeneous. Furthermore, the t-test results show its significance (2-tailed) with a value of 0.006 for equal variances assumed and 0.009 for equal variances not assumed, both of which are> 0.05. The research findings indicate a significant difference between the experimental and control classes. This means that the hypothesis (Ha) is accepted and (Ho) is rejected. Therefore, it can be concluded that the application of Canva-based interactive multimedia has a significant impact on improving children's early reading skills.